2001
DOI: 10.1677/jme.0.0270309
|View full text |Cite
|
Sign up to set email alerts
|

The putative androgen receptor-A form results from in vitro proteolysis

Abstract: Activation domains in the 114 kDa androgen receptor (AR) NH 2 -and carboxyl-terminal regions are thought to contribute to different extents to AR-mediated transactivation. We investigated using anti-peptide antibodies whether smaller AR forms that migrate like the previously described 87 kDa AR-A occur in vivo resulting in constitutive or increased gene activation. Immunoblots of prostate cancer and fibroblast cell culture extracts revealed 114 and 84 kDa AR forms. Antibody mapping indicated the 84 kDa AR lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 52 publications
4
35
1
1
Order By: Relevance
“…Our results differ from the ones reported in the study on colon cancer by Catalano, et al, in that AR-B, was still the dominant AR protein present in all PCa tissues, though the AR-A/B ratio was increased (9). The study by Gregory et al in 2001 did not show any evidence of a functional AR-A isoform (22). However, a later study demonstrated that the overexpression of AR-A reduced DHT-dependent DNA synthesis when transfected together with AR-B in AR-defective HOB and GSF-540 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from the ones reported in the study on colon cancer by Catalano, et al, in that AR-B, was still the dominant AR protein present in all PCa tissues, though the AR-A/B ratio was increased (9). The study by Gregory et al in 2001 did not show any evidence of a functional AR-A isoform (22). However, a later study demonstrated that the overexpression of AR-A reduced DHT-dependent DNA synthesis when transfected together with AR-B in AR-defective HOB and GSF-540 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The weaker band under the 110-kDa AR in lane 5 (Fig. 3A, ii) likely resulted from in vitro proteolytic cleavage of AR, which has been described in prostate cancer cells previously (36).…”
Section: Methodsmentioning
confidence: 55%
“…Caspase-3 is suggested to be the enzyme responsible for the cleavage of this pathologic AR (19)(20)(21)(22). Based on these observations of AR in neurodegenerative diseases, caspase-3 is implicated to cleave AR in prostate cancer cells (15,23). However, we found that, under physiologic conditions, caspase-3 is not present in its activated form in exponentially growing LNCaP cells and caspase-3 is not part of the AR-CaM complex.…”
Section: Discussionmentioning
confidence: 67%
“…First, AR is degraded to small (V10 residues) peptides by the threonine proteases of the ubiquitin-proteasome system (4)(5)(6)(7)(8)(9). Second, AR can be cleaved by serine proteases (10)(11)(12)(13)(14)(15)(16). These studies established that, structurally, AR consists of at least three domains, the ligand-binding domain (LBD), the DNA-binding domain (DBD), and the NH 2 -terminal domain (ATD), separated by protease-sensitive linker regions.…”
Section: Introductionmentioning
confidence: 99%